Pengaruh Board Gender Diversity dan Kepemilikan Institusional terhadap Penghindaran Pajak dengan Corporate Social Responsibility sebagai Variabel Mediasi - Shinta, Septiana Has; Putra, Rosyid Nur Anggara (Shafin: Sharia Finance and Accounting Journal, 2025)
Tax avoidance leads to a decrease in tax revenue, which in turn reduces state revenue. As a result, government programs, including infrastructure development, are not running optimally. This study aims to re examine the factors that influence tax avoidance behavior and analyze the effect of the presence of women on the board of directors, the presence of women on the board of commissioners, and institutional ownership on tax avoidance with corporate social responsibility as a mediating variable. This research was carried out on manufacturing companies in the consumer goods industry listed on the Indonesia Stock Exchange. with a range of years of 2018 - 2023. This sort of quantitative study employs secondary data in the form of annual reports and firm sustainability reports. Purposive sampling selects companies based on specified criteria so that obtained a sample of 162 sample data processed using Eviews 12. The analysis method used is panel data regression of the selected sample. The results of model I data analysis demonstrate that the inclusion of women on the board of commissioners has a detrimental impact on corporate social responsibility. The participation of women on the board of directors and institutional ownership have little effect on corporate social responsibility. Model II data analysis reveals that the presence of women on the board of directors, the presence of women on the board of commissioners, and institutional ownership have no effect on tax evasion. Meanwhile, corporate social responsibility as a mediating variable has a negative effect on tax avoidance Meanwhile, corporate social responsibility does not play a substantial role in moderating the indirect relationship between the presence of women on the board of directors, women on the board of commissioners, and institutional ownership